The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/ismej.2012.15
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of a stable trichloroethene-degrading microbial community

Abstract: Dehalococcoides bacteria are the only organisms known to completely reduce chlorinated ethenes to the harmless product ethene. However, Dehalococcoides dechlorinate these chemicals more effectively and grow more robustly in mixed microbial communities than in isolation. In this study, the phylogenetic composition and gene content of a functionally stable trichloroethene-degrading microbial community was examined using metagenomic sequencing and analysis. For phylogenetic classification, contiguous sequences (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 63 publications
(100 reference statements)
2
55
0
Order By: Relevance
“…This agrees with the observations made using constructed consortia that reductive dechlorination rates are not affected by sulfate amendment (2 and 5 mM) under electron donor limitation. Also, the higher abundance of D. mccartyi (Ͼ30%) in the enrichment culture compared to the co-and tricultures may be another reason that dechlorination outcompetes sulfate reduction (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with the observations made using constructed consortia that reductive dechlorination rates are not affected by sulfate amendment (2 and 5 mM) under electron donor limitation. Also, the higher abundance of D. mccartyi (Ͼ30%) in the enrichment culture compared to the co-and tricultures may be another reason that dechlorination outcompetes sulfate reduction (53).…”
Section: Discussionmentioning
confidence: 99%
“…The methanogenic dechlorinating community ANAS was previously enriched from contaminated soil obtained from the Alameda Naval Air Station (CA). The culture has been maintained in the laboratory for more than 15 years in a continuously stirred semibatch fed reactor, and its community structure and dechlorination performance have been previously described (53,56,57).…”
Section: Methodsmentioning
confidence: 99%
“…The metagenomes of microbial communities are currently under investigation to reveal the metabolic interactions within organohalide-respiring consortia. Some consortia have been developed and characterized for organohalide-respiring populations and associated bacteria (Duhamel and Edwards, 2007;Rowe et al, 2008;Brisson et al, 2012;Hug, 2012;Maphosa et al, 2012). PCR-DGGE analysis using 16S rRNA genes usually yields patterns that reflect the composition of dominant microorganisms, including the nonculturable members (Gelsomino et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Metaanalyses highlighted two high plasticity regions (HPR) around the origin of replication but otherwise the strains show high synteny and identity (1029 genes conserved in all strains) [16,17,18 ,19]. Metagenomes for Dehalococcoides-containing enrichment cultures have also been recently described for the cultures called KB1, DonnaII, and ANAS [20,21].…”
Section: Genomes Of the Specialists: Dehalobacter And Dehalococcoidetesmentioning
confidence: 99%
“…Metagenome analyses of chloroethene-respiring, Dehalococcoides-enriched cultures showed that multiple non-Dehalococcoides populations (e.g. Firmicutes; methanogens; delta-proteobacteria) harbor pathways for cobalamin synthesis [20,21] and Men [63] observed that Dehalococcoides in coculture with Desulfovibrio benefitted from corrinoid salvage and amino acid pathways in the latter organism. Yan [75] showed specific cobamide transfer to Dehalococcoides from G. lovleyi strains but not G. sulfurreducens.…”
Section: Genome-informed Studiesmentioning
confidence: 99%